Identification of LARK as a novel and conserved G-quadruplex binding protein in invertebrates and vertebrates. Issue 14 (5th June 2019) - Niu, Kangkang; Xiang, Lijun; Jin, Ying; Peng, Yuling; Wu, Feng; Tang, Wenhuan; Zhang, Xiaojuan; Deng, Huimin; Xiang, Hui; Li, Sheng; Wang, Jian; Song, Qisheng; et al.
Abstract: Double-stranded DNAs are usually present in the form of linear B-form double-helix with the base pairs of adenine (A) and thymine (T) or cytosine (C) and guanine (G), but G-rich DNA can form four-stranded G-quadruplex (G4) structures, which plays important roles in transcription, replication, translation and protection of telomeres. In this study, a RNA recognition motif (RRM)-containing protein, BmLARK, was identified and demonstrated to bind G4 structures in the promoters of a transcription factor BmPOUM2 and other three unidentified genes of Bombyx mori, as well as three well-defined G4 structures in the human genes. Homologous LARKs from Bombyx mori, Drosophila melanogaster, Mus musculus and Homo sapiens bound G4 structures in BmPOUM2 and other genes in B. mori and H. sapiens . Upon binding, LARK facilitated the formation and stability of the G4 structure, enhancing the transcription of target genes. The G4 structure was visualized in vivo in cells and testis from invertebrate B. mori and vertebrate Chinese hamster ovary (CHO) cells. The results of this study strongly suggest that LARK is a novel and conserved G4-binding protein and that the G4 structure may have developed into an elaborate epigenetic mechanism of gene transcription regulation during evolution.